Complex of nonivasive experimental methods for the microcirculatory system monitoring - Mizeva, I.A.; Goldobin, D.S.; Airikh, D.V. (Perm Federal Research Centre Journal, 2017)
The paper presents the results of an experimental study of the interrelation of measurable parameters which characterize the functional state of the blood microcirculation system. In particular, scale-by-scale correlation of signals, obtained by laser Doppler flowmetry (LDF) and photopletizmography (PPG) is found, which means that spectral decomposition of PPG signals, as well as LDF ones can be used for the detection of microvascular abnormality. The interconnection of optical signals and skin thermometry both at rest and during a loading test is studied. It is shown that the source of temperature disturbances on the surface of the skin is, apparently, blood vessels, lying at a depth of approximately 2 mm. The synchronization of blood flow oscillations of the forearm skin at a distance of 3 cm is studied. It is shown that oscillations with a frequency of 0.1 Hz have high synchronization at rest, and under local heating which causes a local vasodilation reaction, the synchronization decreases to a statistically insignificant level.